Dynamic Crack Propagation and Fracture Behavior of Pre-cracked Specimens under Impact Loading by Split Hopkinson Pressure Bar - Shijun Zhao; Qing Zhang (Advances in Materials Science and Engineering)
Deformation and fracture of brittle materials, especially crack propagation, have drawn wide attention in recent years. But dynamic crack propagation under impact loading was not well understood. In this paper, we experimentally tested Brazilian disk (BD) fine sandstone specimens containing pre-cracks under cyclic impact loading by the Φ 74 mm diameter split Hopkinson pressure bar (SHPB) test device. The pre-cracked specimens were named central straight through crack flattened Brazilian disk (CSCFBD). By using the low air-pressure loading conditions (0.1 MPa, equal to the impact velocity of 3.76 m/s), a series of dynamic impact tests were detected successfully, and the effects of pre-cracks on dynamic properties were analyzed. Experimental results show that the multiple cracks mostly initiate at/or near the pre-crack tips and then propagate in different paths and directions varying by inclination angles, leading to the ultimate failure. Compared to static or quasi-static loading, dynamic crack propagation and fracture behavior are obviously different. Furthermore, we characterized the crack propagation paths, directions, and fracture patterns and discussed the influences of the pre-cracks during the breakage process. We concluded that the results obtained are significant in investigating the failure mechanism and mechanical properties of brittle materials under impact loading.